EFFECT OF REPLACING TREATED AND UNTREATED CORN IMPURITIES WITH UREA INSTEAD OF WHEAT BRAN ON PRODUCTIVE PERFORMANCE OF AWASSI LAMBS - Thaer A. M. Al-Mamouri; J. A. Tawfeeq Al-Ani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The study was conducted to study the effect of replacing different levels of treated and untreated corn impurities with urea instead of wheat bran on productive performance of Awassi lambs. Wheat bran were replaced by five levels of treated and untreated corn impurities as: 44:0%, 32:11%, 20:22%, 10:32% and 0:39% bran: impurities in a 2×5 factorial experiment. Concentrated fed at 3% of live body weight as dry matter basis, while alfalfa hay was offered ad libitum. Forty Awassi lambs were used, with an initial weight of 27.45 ± 2.16 kg and 4-5 months old. All lambs were fed individually feeding for 70 days, preceded by 14 days as adaptation period. Results showed a non-significant superiority in dry matter and nutrients intake by increasing corn impurities and a highly significant increased (p<0.01) in ether extract and ash intake (g/day), with superiority of digestibility (P<0.05) of organic matter% (OM) and crude protein% (CP), feed efficiency, daily gain (g/ day) and total weight gain (kg) for feeding 30% of corn impurities treated with urea (T9). In conclusion, it is possible to use corn impurities instead of wheat bran, preferably treated with urea to increase crude protein content, degraded crude fibers and improved nutritional values.